Trophic sources and pathways of mesozooplankton and fish larvae in the Kuroshio and its neighboring waters based on stable isotope ratios of carbon and nitrogen. (January 2023) - Kobari, Toru; Shinyashiki, Maharu; Saito, Kanako; Kume, Gen; Ichinomiya, Mutsuo; Komorita, Tomohiro; Miyamoto, Hiroomi; Okazaki, Yuji; Makino, Fumihiro; Fukuda, Ryuji; Hyodo, Fujio; Noguchi-Aita, Maki
Highlights: Mesozooplankton have lower δ 13 C and δ 15 N at more pelagic sites. Mesozooplankton δ 15 N to δ 13 C are aligned regardless of the sites. Trophic sources of fish larvae are estimated with mesozooplankton δ 13 C and δ 15 N. Mesozooplankton δ 13 C and δ 15 N represent trophodynamics at lower trophic levels. Abstract: Major forage fishes spend their vulnerable early life stages in the Kuroshio and its neighboring waters where phytoplankton standing stocks are much lower than in coastal areas. Nevertheless, little is known of how mesozooplankton and fish larvae with their high biodiversity are supported in the Kuroshio ecosystem. Here we report stable isotope ratios of carbon (δ 13 C) and nitrogen (δ 15 N) for mesozooplankton and fish larvae from coastal to pelagic sites in the East China Sea to evaluate trophic sources and pathways at lower trophic levels in planktonic food webs under different environmental regimes. Although δ 13 C and δ 15 N in mesozooplankton and fish larvae varied among taxonomic groups and sites, mesozooplankton δ 13 C and δ 15 N tended to be lower for particle-feeders than carnivores and fish larvae and at more pelagic sites than in coastal waters. There were significant linear regressions between δ 15 N and δ 13 C of mesozooplankton communities, with the similar slopes among sites and lower intercepts at more pelagic sites. The δ 15 N and δ 13 C of small copepods, euphausiids, ostracods, appendicularians and fish larvae were aligned close to the regression line covering all regions, indicating that these were trophic sources and pathways to mesozooplankton and fish larvae. Our results suggest that trophic sources of mesozooplankton and fish larvae are supported through copepods and appendicularian-integrated microbial production and are more dependent on diazotrophic production in more pelagic waters.